ANALISIS EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 RAMBATAN, TANAH DATAR - Zulfawan Syafri (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
The purpose of the study was to describe the instructional process of Islamic Education subject in State High School 1 Rambatan. This research was qualitative. The subjects of the study was the Islamic education teachers that consist of 3 teachers. The instruments of data collection were observation and documentation. Data were analyzed by using matrix analysis or logic analysis Glaser and Strauss. The results showed that the instructional process of Islamic Education subject in State High School 1 Rambatan was good category by observation score 66,24. Keywords: Evaluation, Instructional Process, Islamic Education Subject, High School, Rambatan